2010
DOI: 10.1016/j.mib.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The future of the β-lactams

Abstract: In the 80 years since their discovery the β-lactam antibiotics have progressed through structural generations, each in response to the progressive evolution of bacterial resistance mechanisms. The generational progression was driven by the ingenious, but largely empirical, manipulation of structure by medicinal chemists. Nonetheless, the true creative force in these efforts was Nature, and as the discovery of new β-lactams from Nature has atrophied while at the same time multi-resistant and opportunistic bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
118
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 59 publications
0
118
0
1
Order By: Relevance
“…These enzymes catalyze the hydrolysis of the amide bond in the ␤-lactam ring characteristic of this family of drugs (1)(2)(3)(4)(5). MBLs are metal-dependent hydrolases which generally use Zn(II) as a Lewis acid to activate a water molecule for the nucleophilic attack.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes catalyze the hydrolysis of the amide bond in the ␤-lactam ring characteristic of this family of drugs (1)(2)(3)(4)(5). MBLs are metal-dependent hydrolases which generally use Zn(II) as a Lewis acid to activate a water molecule for the nucleophilic attack.…”
mentioning
confidence: 99%
“…Crystal structures of MBLs from the three subclasses have revealed that these enzymes present a common ␣␤/␤␣ sandwich fold, with the active site located within a groove at the interface between these two halves (1-6). The Zn(II)-binding residues vary among different subclasses, giving rise to diverse metal site architectures and metal contents required for activity (1)(2)(3)(4)(5)(6). B1 and B3 MBLs are broad-spectrum enzymes that hydrolyze penicillins, cephalosporins, and carbapenems with a wide variety of in vitro catalytic efficiencies, displaying a broad range of resistance profiles in vivo (1)(2)(3)(4)(5)8).…”
mentioning
confidence: 99%
“…Family M56, in turn, includes BlaR1 from Staphylococcus aureus and Bacillus licheniformis, and MecR1 from S. aureus. They function as parts of the signal transduction systems that trigger bacterial resistance to ␤-lactam antibiotics, a phenomenon that poses a serious threat to animal and human health and is exerted through the synthesis of a ␤-lactamase or a penicillinbinding protein (21)(22)(23)(24)(25)(26)(27)(28). BlaR1 and MecR1 are composed of an N-terminal IMMP domain facing the cytosol and a C-terminal extracellular sensor domain that binds environmental ␤-lactams (29 -32).…”
mentioning
confidence: 99%
“…One of these approaches is to expand the use of antibiotics by using them in combination with compounds that inhibit resistance pathways [5]. For example, clavulanic acid, tazobactam and sulbactam are β-lactamase inhibitors that have been used successfully in combination with β-lactams antibiotics, and they have prolonged and expanded their effectiveness [6][7][8]. Aminoglycoside, macrolide and lincosamide antibiotics are also susceptible to enzyme-mediated deactivation through phosphorylation by kinases [9][10][11][12][13].…”
mentioning
confidence: 99%